Seeds for democracy: understanding European values in educational dialogues - Schwarz, Baruch B.; Baker, Michael; Brandel, Noa (Frontiers in Education, 2025)
An analytical framework for observing ethical learning in schoolchildren during social interaction has been recently developed. It comprises two tools for appraising ethical thinking and behaviour: dialogue on ethics (DoE) and ethics of dialogue (EoD). Studying the effectiveness of a project aimed at promoting ethical learning of socially-oriented values—empathy, inclusion, and tolerance—within the context of dialogic education, has appeared as providing a complex picture: the relation between children’s DoE and their EoD was positive where the topic posed for discussion presented a dilemma. In contrast, it was negative when the discussion was conceptual, and the teacher was dominant. In the present paper, we describe a case study to illustrate and explain these results. The DoE/EoD analytical framework was adopted to observe when and why ethical thinking and conduct could be coordinated. The case study shows that ethical learning in its epistemological and behavioural dimensions can be promoted or inhibited in contexts of dialogic education, depending on design principles.